The book of buttons - Whittemore, Joyce (New York : Dorling Kindersley, 1997)
History of buttons and how to choose and use buttons for maximum decorative effect.
Includes index.
Booklist.
Kliatt.
School Library Journal.
Adult
Keywords: Button craft; Buttons; Clothing and dress; Button craft; Buttons; Clothing and dress